Southern Sudan Referendum Was Timely, Fair, Peaceful, Credible, Chair of Monitoring Panel Tells Security Council Abyei, Popular Consultations in Blue Nile, Southern Kordofan States among Outstanding Tasks, Head of United Nations Mission Says (Tufts Archival Research Center, 2005)
This document is about the 6468th meeting in the Security Council praising the conduct of the referendum in Sudan. It includes briefings by Benjamin Mkapa, Chair of the Secretary-General's Panel on the Referenda, Haile Menkerios, the Special Representative of the Secretary-General and Head of the United Nations Mission in the Sudan (UNMIS), and several United Nations representatives.